2011
DOI: 10.1242/dev.066282
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine Pax6 activity regulates oligodendrocyte precursor cell migration in the chick embryonic neural tube

Abstract: Homeoprotein transcription factors play fundamental roles in development, ranging from embryonic polarity to cell differentiation and migration. Research in recent years has underscored the physiological importance of homeoprotein intercellular transfer in eye field development, axon guidance and retino-tectal patterning, and visual cortex plasticity. Here, we have used the embryonic chick neural tube to investigate a possible role for homeoprotein Pax6 transfer in oligodendrocyte precursor cell (OPC) migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 39 publications
5
53
0
Order By: Relevance
“…Interestingly, in addition to its established cellautonomous roles, Pax6 has demonstrated an unexpected paracrine effect in different CNS tissues (Di Lullo et al, 2011;Lesaffre et al, 2007). Whether Pax6 acts similarly in the early hindbrain is not known and requires further understanding of how Pax6 acts as a signaling molecule.…”
Section: Possible Mechanisms Of Pax6 Activitymentioning
confidence: 99%
“…Interestingly, in addition to its established cellautonomous roles, Pax6 has demonstrated an unexpected paracrine effect in different CNS tissues (Di Lullo et al, 2011;Lesaffre et al, 2007). Whether Pax6 acts similarly in the early hindbrain is not known and requires further understanding of how Pax6 acts as a signaling molecule.…”
Section: Possible Mechanisms Of Pax6 Activitymentioning
confidence: 99%
“…It was shown that En1/2 cooperates with EphrinA5 in the optic tectum and with DPP in the fly wing disc [14,16,17]. A similar synergy was found between Pax6 and Netrin signalling in the ventral neural tube [13]. The essence of this synergy, illustrated in figure 3, is based on the hypothesis that HPs sensitize the classical receptors to otherwise inefficient concentrations of their agonists.…”
Section: Perspectivesmentioning
confidence: 71%
“…Blocking the passage of Pax6 in vivo by local expression of a single-chain antibody (aPax6-scfv) or by injection of a monoclonal anti-Pax6 antibody at the midblastula stage prevents the extension of the eye anlagen in the zebrafish and leads to defects in eye development [12]. Another recently discovered non-cell-autonomous embryonic function of Pax6 is to enhance oligodendrocyte precursor cell migration in the chick neural tube [13].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, this does not mean that they actually do it or that in vitro results can be generalized to in vivo situations. However, intercellular transfer has been demonstrated in vivo for Engrailed1, Engrailed2, Otx2, and Pax6, the four proteins that were analyzed from a physiologic point of view (Lesaffre et al, 2007;Sugiyama et al, 2008;Wizenmann et al, 2009;Di Lullo et al, 2011;Beurdeley et al, 2012;Yoon et al, 2012). Thus, we are confident that HP signaling is a very general and important phenomenon.…”
Section: Introduction: the History Of Homeoprotein Transductionmentioning
confidence: 83%
“…In vivo, the situation might be different because of the presence of HP binding sites (Beurdeley et al, 2012) that can trap the proteins and regulate their internalization. From this point of view, of note, whenever the quantification was done, ;5% of the HPs were at the cell surface, compared with 95% in the intracellular compartments (Wizenmann et al, 2009;Di Lullo et al, 2011) …”
Section: Penetratin Homeodomain and Homeoprotein Internalizationmentioning
confidence: 99%